Breastfeeding problems and solutions - Jamani, Nurjasmine Aida (2015)
During early weeks of delivery, many mothers experienced problems in lactation. This can lead to frustration which eventually lead to early weaning and even depression. Problems may happen throughout the journey even though the mother is approaching the end of her breastfeeding journey.